Evolution and technical efficiency of land tenure systems in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2002)
The degree to which prevailing land tenure arrangements in sub-Saharan Africa constrain efficiency and agricultural productivity are still not determined. This paper examines the sources of economic efficiency (inefficiency) of alternative land tenure arrangements in Ethiopia using stochastic frontier production function. The results show that sharecropped and borrowed land are technically less efficient than owner-cultivated or fixed rental land due to restrictions imposed on them by landowners and the interactions of land market with other imperfect and absent input markets. Thus, a policy has to be drawn to facilitate more efficient transactions of land between farmers and to minimise inefficiencies associated with these tenure systems.